Apoptosis induction of HT-29 human colorectal adenocarcinoma cells in-vitro and anti-tumor activity against colon cancer of newcastle disease virus strains AF2240 and V4-UPM - Rowa Mohammed Assayaghi
Newcastle disease virus (NDV) is a negative-sense single standard RNA virus of the Paramyxoviridae family that causes severe disease in several avian species. Several NDV strains have been investigated for their anti-cancer effects because it can replicate up to 1000 times better in human neoplastically transformed cells than in most normal human cells. Since treatment of cancer patient with chemo-radiotherapy caused severe side effects due to cytotoxic effects towards normal tissues which often is resulting in morbidity. NDV strains AF2240 and AF2240 and V4-UPM were shown to be cytolytic against various cancer cell in-vitro and very effective as antileukemic agents. Therefore in this thesis both NDV strains were evaluated for their cytolytic effect on human colon cancer cells in-vitro and in-vivo effects against chemical induced colon cancer in rats. In this study, the cytolytic affects and apoptosis induction of NDV strains AF2240 and V4-UPM against HT-29 human colorectal adenocarcinoma cells were carried out. Moreover effects of both virus strains on the aberrant crypt foci (ACF) and some colon cancer marker expressions of induced colon cancer in-vivo were also studied. The CD50 values for cytolytic effects of NDV strains AF2240 and strain V4-UPM on HT-29 by using MTT assay were 16.0 and 33.0 HAU/mL, respectively. However, the same titers of virus strains did not give significant cytolytic effects on the normal mouse fibroblasts (3T3) cells. Apoptosis and necrosis cell death modes were evaluated base on the morphological changes observed under the phase contrast light and fluorescent microcopies after staining with acridine orange and propidium iodide (AO/PI). Both NDV strains included apoptosis cell death to the HT-29 cells. The percentage of apoptotic cells were increased in the time dependent manner as compared to variable and necrotic cells. The intrinsic and extrinsic apoptosis pathway were determind by assasing the related capases activities and studying the expression of some apoptotic genes. A significant activation of caspase-9, an initiator caspase for the instrinsic pathway compared to caspase-8 was observed. Moreover, RT-PCR results showed Bax expression was up-regulated in HT-29 cells that treated with both NDV strains while down-regulatd was observed in non-treated HT-29 cells. In contrast, Bcl-2 expression was up-regulated in non-treated cells and down-regulated in HT-29 cells that were treated with both NDV strains. The results suggest that NDV-induced apoptosis through intrinsic (mitochondrial) pathway of HT-29 human colorectal adenocarcinoma cells. Anti-tumor activity of NDV strains AF 2240 and V4-UPM were evaluated in-vivo by different doses of NDV on the development of aberrant crypt foci (ACF) in Sprague-Dawley rats initiated with the colon carcinogen Azoxymethane (AOM). The total number and crypt multiplicity of ACF were significantly decreased in NDV treated group groups as compared to non-treated rats. The efficacy of the combination treatment of NDV on the development of ACF in rats' colon was also investigated. Histopatholgical study was carried out to confirm results of methylene blue method. The severe dysplasia od ACF was only found and observed in the non-treated group, while mild and moderate dysplasia of ACF were exhibited in other groups. The number and degree of dyspasia of AFC were significantly decreased in the combination treatment of NDV and 5-FU, 5-FU only and high doses NDV. The interaction between COX-1 and COX-2 genes in rats that were treated with different doses of NDV strains and 5-FU was elucidated. COX-2 expression was up-regulated in positive control and low doses NDV groups compared to other groups. The above results have confirmed that NDV strains AF 2240 and V4-UPM were cytolytic against HT-29 human colorectal adenocarcinoma cells in-vitro and very effective in reducing ACF induced colon cancer in-vivo.